Boron nitride ceramic and nickel-based superalloy connecting joint and preparation method thereof

CN121377808BActive Publication Date: 2026-10-30CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511569665.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-10-30
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

[0004]鉴于上述的分析,本发明实施例旨在提供一种氮化硼陶瓷与镍基高温合金的连接接头及其制备方法,用以解决现有技术不存在将氮化硼陶瓷与镍基高温合金从微观层面进行有效、高强度连接的结构的问题中的至少一个

Benefits of technology

[0024]1、与现有技术比较,本发明首次提出了氮化硼陶瓷与镍基高温合金的连接接头,所述连接接头含有由含镍的钎料与氮化硼反应后生成的钎料-氮化硼反应层,使化学惰性较强的氮化硼陶瓷与镍基高温合金从微观层面实现有效结合,其中,所述钎料-氮化硼反应层中含有的TiN、TiB2能够改善了BN陶瓷与钛或钛合金的界面润湿,在所述BN陶瓷与所述钎料反应层之间提供化学键合,起到强化相的作用,增强界面结合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377808B_ABST
    Figure CN121377808B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of boron nitride ceramic and the connecting joint of nickel-based superalloy and its preparation method, belong to ceramic / metal composite structure technical field, solve the problem that the effective, high-strength connection structure of boron nitride ceramic and nickel-based superalloy from micro level does not exist in prior art.The connecting joint includes boron nitride ceramic, intermediate layer and nickel-based superalloy connected in sequence, the intermediate layer includes brazing material-boron nitride reaction layer, brazing material reaction layer, brazing material-nickel-based superalloy reaction layer;TiN is contained in brazing material-boron nitride reaction layer;Brazing material-boron nitride reaction layer in the connecting joint of the application can effectively connect boron nitride ceramic and nickel-based superalloy;By boron nitride-Ti layer reaction layer, Ti layer, brazing material-Ti layer reaction layer can make boron nitride ceramic and nickel-based superalloy realize high-strength connection;The connecting joint can promote boron nitride ceramic to be effectively applied in aerospace, nuclear energy and other fields high-temperature thermal structure material heat management.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic / metal composite structure technology, and in particular to a connecting joint between boron nitride ceramic and nickel-based superalloy and its preparation method. Background Technology

[0002] Composite structures of ceramic and metal materials can combine the advantages of both ceramics and metals while compensating for each other's disadvantages, thereby achieving comprehensive superior performance that cannot be achieved by a single material, such as excellent strong and tough bonding performance, excellent wear resistance, high heat resistance and thermal shock resistance, synergistic and optimized functional characteristics, and strong designability.

[0003] Due to the differences in physicochemical properties between ceramics and metals, it is difficult to effectively and strongly bond the two. The high melting point and brittleness of ceramics make it impossible to achieve an effective connection using traditional fusion welding and pressure welding. Currently, although brazing uses filler metals with lower melting points to effectively connect some ceramics (such as SiC and Si3N4) to metals through interfacial reactions, the inertness of boron nitride ceramics means that it hardly undergoes an interfacial reaction with existing filler metals, making it difficult to achieve an effective connection. Therefore, there is currently no joint for connecting boron nitride ceramics to nickel-based superalloys, which limits the application of boron nitride ceramics in the thermal management of high-temperature thermal structural materials. Summary of the Invention

[0004] In view of the above analysis, the present invention aims to provide a connection joint between boron nitride ceramic and nickel-based superalloy and its preparation method, so as to solve at least one of the problems in the prior art of not having a structure for effectively and strongly connecting boron nitride ceramic and nickel-based superalloy at the microscopic level.

[0005] On one hand, embodiments of the present invention provide a connection joint for boron nitride ceramic and nickel-based superalloy. The connection joint includes boron nitride ceramic, an intermediate layer and a nickel-based superalloy connected in sequence. In the direction from the boron nitride ceramic to the nickel-based superalloy, the intermediate layer includes a solder-boron nitride reaction layer, a solder reaction layer and a solder-nickel-based superalloy reaction layer; the solder-boron nitride reaction layer contains TiN.

[0006] Furthermore, the solder-boron nitride reaction layer includes a boron nitride-Ti layer reaction layer, a Ti layer, and a solder-Ti layer reaction layer.

[0007] Furthermore, the boron nitride ceramic is a hexagonal boron nitride ceramic.

[0008] Furthermore, the boron nitride ceramic is in the form of sheets or blocks.

[0009] Furthermore, the boron nitride-Ti layer reaction layer contains TiN;

[0010] Furthermore, the thickness of the boron nitride-Ti reaction layer is 0.1-0.5 μm.

[0011] Furthermore, the thickness of the titanium layer is 1-4 μm.

[0012] Furthermore, the thickness of the solder-Ti layer reaction layer is 0.1-0.5 μm.

[0013] Furthermore, the raw materials of the solder reaction layer contain nickel-based amorphous powder and titanium hydride powder, with a mass ratio of 9:1 to 7:3.

[0014] Furthermore, the thickness of the solder reaction layer is 20-200 μm.

[0015] Furthermore, the brazing filler metal-nickel-based superalloy reaction layer is a metal cladding layer;

[0016] Furthermore, the thickness of the metal cladding layer is 5-25 μm.

[0017] Furthermore, the shear strength of the connecting joint is 0.4-4 MPa.

[0018] On the other hand, embodiments of the present invention provide a method for preparing the connecting joint between the boron nitride ceramic and the nickel-based superalloy, the method comprising:

[0019] (1) Preparation of nickel-based composite solder;

[0020] (2) Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it with a mold;

[0021] (3) Heat treatment to obtain the connecting joint.

[0022] Furthermore, prior to step (2), a titanium film is deposited on the surface of the boron nitride ceramic to be welded.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] 1. Compared with the prior art, this invention proposes for the first time a connecting joint between boron nitride ceramic and nickel-based superalloy. The connecting joint contains a solder-boron nitride reaction layer formed by the reaction of nickel-containing solder and boron nitride, which enables the chemically inert boron nitride ceramic and nickel-based superalloy to achieve effective bonding at the microscopic level. The TiN and TiB2 contained in the solder-boron nitride reaction layer can improve the interfacial wetting between BN ceramic and titanium or titanium alloy, provide chemical bonding between BN ceramic and solder reaction layer, and play the role of reinforcing phase to enhance interfacial bonding.

[0025] 2. The present invention adjusts the composition and structure of the solder-boron nitride reaction layer. On the one hand, the TiN and TiB2 contained in the boron nitride-Ti layer reaction layer can improve the bonding strength between the boron nitride ceramic and the Ti layer. At the same time, the metal cladding layer between the solder and the Ti layer can jointly achieve an effective and high-strength connection between the boron nitride ceramic and the solder reaction layer. On the other hand, the multi-layer structure constituting the solder-boron nitride reaction layer has different coefficients of thermal expansion, so that the joint between the ceramic and the solder has gradient thermal stress behavior, reducing the excessively concentrated thermal stress between them, improving the thermal stability of the joint during actual use, and extending its service life.

[0026] 3. The present invention adjusts the thickness of each layer of the intermediate layer constituting the connecting joint, which can ensure an effective and high-strength connection between boron nitride ceramic and nickel-based high-temperature alloy, while avoiding interface embrittlement caused by an excessively thick intermediate layer and reducing the mechanical strength of the connecting component.

[0027] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0028] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0029] Figure 1 This is a schematic diagram of the connection connector of the present invention;

[0030] Figure 2 Here is a SEM image of the connector of this invention;

[0031] Figure 3 This is a physical diagram of the connector of the present invention;

[0032] Figure 4 A schematic diagram illustrating the process for preparing the connector of the present invention;

[0033] Figure label:

[0034] 1-Ni-based superalloy; 2-Ni-based superalloy-brazing reactant layer; 3-Brazing solder layer; 4-Brazing solder-Ti reactant layer; 5-Ti layer; 6-Ti layer-boron nitride reactant layer; 7-BN ceramic. Detailed Implementation

[0035] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0036] Boron nitride ceramics possess extremely high thermal stability and excellent thermal conductivity, making them promising materials for thermal management in high-temperature thermal structural materials. They are also promising materials in aerospace, nuclear energy, and other fields. However, the application of boron nitride ceramics often requires bonding with metals. The inertness of boron nitride ceramics makes it difficult for them to react with existing low-temperature brazing fillers, and it is impossible to effectively connect boron nitride ceramics with metal high-temperature thermal structural materials through brazing. In addition, the significant difference in the coefficients of thermal expansion between boron nitride ceramics and metals further hinders the connection between the two.

[0037] Therefore, this invention discloses a connection joint between boron nitride ceramic and nickel-based superalloy, as shown in the schematic diagram below. Figure 1 As shown, the connector comprises a boron nitride ceramic, an intermediate layer, and a nickel-based superalloy connected in sequence. In the direction from the boron nitride ceramic to the nickel-based superalloy, the intermediate layer comprises a solder-boron nitride reaction layer, a solder reaction layer, and a solder-nickel-based superalloy reaction layer; the solder-boron nitride reaction layer contains TiN.

[0038] Compared with existing technologies, this invention proposes for the first time a joint connecting boron nitride ceramics and nickel-based superalloys. The joint contains a solder-boron nitride reaction layer formed by the reaction of nickel-containing solder and boron nitride, which enables effective bonding of the chemically inert boron nitride ceramics and nickel-based superalloys at the microscopic level. The TiN and TiB2 contained in the solder-boron nitride reaction layer can improve the interfacial wetting between the BN ceramics and titanium or titanium alloys, provide chemical bonding between the BN ceramics and the solder reaction layer, and act as a reinforcing phase to enhance interfacial bonding.

[0039] It should be noted that, taking into account the thermal stability and thermal conductivity of boron nitride, as well as processing feasibility and economic cost, this invention needs to limit the type of boron nitride.

[0040] Specifically, the boron nitride ceramic described in this invention is a hexagonal boron nitride ceramic.

[0041] It should be noted that, in order to adapt to the application of boron nitride ceramics in the thermal management of high-temperature thermal structural materials, the present invention needs to define the structural shape of boron nitride ceramics.

[0042] Specifically, the boron nitride ceramic of the present invention is in the form of sheets or blocks.

[0043] It should be noted that, in order to enhance the effective connection between the boron nitride ceramic and the solder, the present invention designs a multi-layer structure for the solder-boron nitride reaction layer between the two.

[0044] Specifically, the solder-boron nitride reaction layer includes a boron nitride-Ti layer reaction layer, a Ti layer, and a solder-Ti layer reaction layer.

[0045] It should be noted that, in order to improve the effective connection between the boron nitride ceramic and the Ti layer, and at the same time avoid interface embrittlement, the present invention needs to adjust the composition and thickness of the boron nitride-Ti layer reaction layer obtained by the reaction of the two.

[0046] Specifically, the boron nitride-Ti layer reaction layer contains TiN and TiB2. During the preparation process, nitrogen diffuses much faster than boron, making it easier for nitrogen to react with titanium from the boron nitride ceramic side to form TiN. Boron, on the other hand, reacts relatively slowly and accumulates on the side closer to BN to form TiB2.

[0047] It should be noted that TiN has a face-centered cubic structure, high hardness, high chemical stability, excellent metallic conductivity, and good lattice matching with Ti, effectively blocking the further diffusion of B atoms into the Ti matrix and inhibiting the excessive growth of the reaction layer; its coefficient of thermal expansion is between that of Ti and TiB2 / BN, which helps to alleviate thermal mismatch stress; compared with TiB2, TiN has a certain degree of toughness and can prevent crack propagation.

[0048] It should be noted that TiB2 (titanium diboride) has a hexagonal structure, exhibiting extremely high hardness, high melting point, high wear resistance, excellent metallic electrical and thermal conductivity, and is a major contributor to interfacial strength. It has a similar crystal structure to BN (both are hexagonal) and exhibits crystallographic continuity with BN. It can form strong chemical bonds with BN, acting as an "anchor point" to BN ceramics, effectively transferring loads from the relatively soft titanium matrix to the hard BN ceramics.

[0049] Specifically, the thickness of the boron nitride-Ti reaction layer is 0.1-0.5 μm. If the thickness is too large, it will cause it to detach from the boron nitride substrate; if the thickness is too small, it will be impossible to form a good and stable connection. The thickness can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm.

[0050] It should be noted that, in order to improve the effective connection between boron nitride ceramic and solder, while alleviating the concentration of interfacial thermal stress and preventing interfacial embrittlement, the present invention needs to limit the thickness of the titanium layer.

[0051] More specifically, the thickness of the titanium layer is 1-4 μm. If the titanium layer is too thick, it will cause delamination and fracture of the titanium layer itself; if the titanium layer is too thin, it will lose its thermal stress relief effect. The thickness can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.

[0052] It should be noted that, in order to ensure the connection strength between the Ti layer and the solder layer while avoiding interface embrittlement, the present invention needs to limit the thickness of the solder-Ti layer reaction layer.

[0053] Specifically, the thickness of the solder-Ti reaction layer is 0.1-0.5 μm. If the reaction layer thickness is too large, it will lead to interface brittleness and lower joint strength; if the reaction layer thickness is too small, it will prevent the formation of an effective connection. The thickness can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm.

[0054] It should be noted that, in order to obtain the weld joint with the best performance, the present invention needs to limit the thickness of the brazing filler metal reaction layer.

[0055] Specifically, the thickness of the solder reaction layer is 20-200 μm. If the solder reaction layer is too thick, the solder reaction will be insufficient, resulting in excessive interfacial compounds and reduced joint strength; if the solder reaction layer is too thin, an effective connection cannot be achieved. The thickness can be 20 μm, 40 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, or 200 μm.

[0056] It should be noted that, in order to achieve a better connection, the present invention needs to limit the thickness of the metal cladding layer, which serves as the brazing filler metal-nickel-based superalloy reaction layer.

[0057] Specifically, the thickness of the metal cladding layer is 5–25 μm. If the solder-nickel-based superalloy reaction layer is too large, it will cause corrosion of the base material and affect the performance of the base material; if the solder-nickel-based superalloy reaction layer is too small, it will result in low bonding strength. The thickness can be 5 μm, 10 μm, 15 μm, 20 μm, or 25 μm.

[0058] It should be noted that the boron nitride ceramic and nickel-based superalloy connection joint provided by the present invention not only achieves an effective connection between the boron nitride ceramic and the nickel-based superalloy, but also achieves a high-strength connection through structural optimization.

[0059] Specifically, the shear strength of the connecting joint is 0.4-4 MPa.

[0060] On the other hand, the present invention also provides a method for preparing the connecting joint between the boron nitride ceramic and the nickel-based superalloy, the specific process flow of which is as follows: Figure 4 As shown, the method includes:

[0061] (1) Preparation of nickel-based composite solder;

[0062] (2) Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it with a mold;

[0063] (3) Heat treatment to obtain the connecting joint.

[0064] It should be noted that in order to improve the adhesion strength of the titanium film on the BN ceramic surface and the wettability of the solder on the Ni-based superalloy surface, it is necessary to remove contaminants from both solder surfaces. The contaminants are one or more of the following: oxide film, adsorbed water film, organic oil, and metal debris.

[0065] Specifically, before step (1), the surfaces of the boron nitride ceramic and the nickel-based high-temperature alloy to be welded are polished and cleaned respectively.

[0066] According to some preferred embodiments of the present invention, the surfaces of boron nitride ceramic and nickel-based high-temperature alloy to be welded are polished with 1000-grit sandpaper and then ultrasonically cleaned with acetone for 10 minutes.

[0067] It should be noted that, in order to enable the chemically inert boron nitride ceramic to not only undergo interfacial reaction with the brazing filler metal and achieve effective bonding with nickel-based superalloys, but also to enhance this effective bonding, the present invention requires modification treatment of the test surface of the boron nitride ceramic.

[0068] Specifically, before step (2), a titanium film is deposited on the surface of the boron nitride ceramic to be welded.

[0069] It should be noted that in the subsequent vacuum heat treatment of joining BN ceramic and Ni-based superalloy using nickel-based composite solder, the titanium film reacts with BN on one side to form a TiN thin layer. TiN has good wetting and pinning effects on boron nitride, which improves the bonding strength between the titanium layer and the BN ceramic. On the other hand, the titanium layer away from the BN ceramic reacts with the nickel-based composite solder to form intermetallic compounds such as TiNi. Simultaneously, the nickel-based composite solder and Ni-based superalloy undergo high-temperature solid solution treatment. The titanium nitride layer, the titanium layer, and the reacted intermetallic compound layer provide a gradient material with different coefficients of thermal expansion, significantly reducing the interfacial thermal stress generated during heat treatment to join the ceramic and metal, thereby achieving effective bonding.

[0070] It should be noted that, in order to improve the adhesion and density of the titanium film on the ceramic surface and to precisely control the film thickness at the micro-nano level, the present invention uses magnetron sputtering to deposit a titanium film on the surface of the boron nitride ceramic to be welded after cleaning.

[0071] More specifically, in step (2), the present invention uses magnetron sputtering to deposit a titanium film on the surface of the boron nitride ceramic to be welded after cleaning, under the following conditions: vacuum degree of 5×10 -5 Pa-7×10 -5The argon pressure range is 0.5Pa-2Pa, the target distance is 100-190mm, the DC power supply power is 180W-220W, and the time is 2-8h.

[0072] It should be noted that, in order to prevent the titanium film from being oxidized during the preparation process, the present invention needs to limit the base vacuum level of magnetron sputtering; appropriate argon pressure, target distance, and power supply can work together to ensure the adhesion, uniformity, and density of the titanium film; the length of sputtering time determines the thickness of the titanium film.

[0073] According to some preferred embodiments of the present invention, the vacuum degree of magnetron sputtering of the present invention can be 5 × 10⁻⁶. -5 Pa-7×10 -5 Any value within the Pa range, such as 5 × 10 -5 Pa, 5.5 × 10 -5 Pa, 6×10 -5 Pa, 6.5 × 10 -5 Pa, 7×10 -5 Pa.

[0074] According to some preferred embodiments of the present invention, the argon gas pressure of the magnetron sputtering of the present invention can be any value in the range of 0.5Pa-2Pa, such as 0.5Pa, 0.8Pa, 1Pa, 1.2Pa, 1.5Pa, 1.7Pa, 2Pa; the target distance of the magnetron sputtering of the present invention can be any value in the range of 100-190mm, such as 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm; and the DC power supply power of the magnetron sputtering of the present invention can be any value in the range of 180W-220W, such as 180W, 190W, 200W, 210W, 220W.

[0075] It should be noted that, in order to facilitate the effective (crack-free interface) and high-strength connection between BN ceramic and Ni-based high-temperature metal through the interfacial reaction between the titanium layer and the ceramic surface, and the interfacial reaction between the titanium layer and the composite solder during subsequent heat treatment, this invention needs to limit the thickness of the titanium film deposited on the BN ceramic surface.

[0076] Specifically, in step (2), the thickness of the titanium film is 1-4 μm.

[0077] According to some preferred embodiments of the present invention, the thickness of the titanium film can be any value within the range of 1-4 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, and 4 μm. If the titanium film is too thin, it will be completely reacted by the BN ceramic and the brazing filler metal during the subsequent heat treatment of brazing, making it impossible to form an intermediate layer with a sufficiently gradient structure between the ceramic to be welded and the nickel-based superalloy, leading to joint failure due to internal stress. If the titanium film is too thick, the joint will also fail due to the poor strength of the titanium film itself. Within the thickness range defined by the present invention, a higher connection strength can be obtained.

[0078] It should be noted that, in order to prevent excessive reaction between the nickel-based amorphous powder solder and the titanium film during the brazing heat treatment process, which would affect the interfacial reaction and bonding strength between the titanium film and boron nitride, the composition of the solder needs to be designed in this invention.

[0079] Specifically, in step (3), the nickel-based composite solder comprises nickel-based amorphous powder and titanium hydride powder, and the mass ratio of the nickel-based amorphous powder to the titanium hydride powder is 7:3 to 9:1.

[0080] It should be noted that, compared with pure Ti, the titanium hydride in the composite brazing filler metal of this invention has higher chemical stability. It is not easily oxidized during the ball milling and mixing process with Ni-based amorphous powder and during the subsequent heat treatment brazing process. Moreover, it can dehydrogenate to form titanium at temperatures above 400°C, which can efficiently participate in the interfacial reaction of brazing and give full play to its regulatory role. This is more conducive to the effective and high-strength connection between BN ceramics and Ni-based superalloys.

[0081] According to some preferred embodiments of the present invention, the mass ratio of the nickel-based amorphous powder to the titanium hydride powder in the titanium film can be any value within the range of 7:3 to 9:1, such as 7:3, 7.5:2.5, 8:2, 8.5:1.5, or 9:1. Too little titanium hydride content will cause the nickel-based amorphous solder to react with the titanium hydride without reacting with the titanium layer, resulting in a decrease in the bonding strength between the titanium layer and the solder layer. Too much titanium hydride content will lead to a higher melting point of the solder and an excessive amount of brittle phase compounds in the joint, reducing the joint strength. Within the solder content range described above in the present invention, a joint with better welding quality can be obtained.

[0082] It should be noted that, by weight percentage, the nickel-based amorphous powder contains 2.75%-3.5% B, 4%-5% Si, 6.0%-8.0% Cr, 2.5%-3.5% Fe, ≤0.06% carbon, and the balance is Ni.

[0083] It should be noted that, in order to ensure that the components of the composite solder are fully and uniformly mixed, the present invention needs to limit the mixing method of the nickel-based amorphous powder and the titanium hydride powder.

[0084] Specifically, in step (3), the nickel-based composite brazing filler metal is obtained by vacuum ball milling and mixing the raw materials. The specific method includes: placing nickel-based amorphous brazing filler metal powder and titanium hydride powder in a vacuum ball milling jar according to the mass ratio of 10:1-20:1, evacuating the jar, injecting nitrogen for protection, and ball milling at 80-120 rpm for 10-30 min under a nitrogen atmosphere of 0.1-0.3 MPa.

[0085] According to some preferred embodiments of the present invention, the ball-to-powder ratio can be any value in the range of 10:1 to 20:1, such as 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1. If the ball-to-powder ratio is too low, it is easy to cause uneven mixing; if the ball-to-powder ratio is too high, it will cause excessive grinding energy, smaller powder size, and poor mixing.

[0086] It should be noted that, in order to prevent the oxidation of the brazing filler metal during the ball milling process, nitrogen gas needs to be injected into the vacuum-sealed ball mill jar for protection, so that the raw materials are mixed in a nitrogen atmosphere of 0.1-0.3 MPa.

[0087] According to some preferred embodiments of the present invention, the nitrogen pressure in the ball mill can be any value in the range of 0.1-0.3 MPa, such as 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, or 0.3 MPa. If the pressure is too low, it is easy to cause the raw material to oxidize in the ball mill. If the pressure is too high, it will cause the powder to spray out due to pressure relief during the opening process.

[0088] According to some preferred embodiments of the present invention, the ball milling speed can be any value within the range of 80-120 rpm, such as 80 rpm, 85 rpm, 90 rpm, 95 rpm, 100 rpm, 105 rpm, 110 rpm, 115 rpm, and 120 rpm. If the speed is too high, it is easy to cause the raw materials to separate and the mixing to be uneven; if the speed is too low, the mixing efficiency is low and the ball milling time is long.

[0089] According to some preferred embodiments of the present invention, the ball milling time can be any value in the range of 10-30 min, such as 10 min, 15 min, 20 min, 25 min, or 30 min. If the time is too short, the mixing will be uneven; if the time is too long, the raw materials will easily separate and the mixing will be uneven.

[0090] It should be noted that, in order to improve the efficiency of subsequent vacuum brazing, the present invention needs to limit the size of the nickel-based amorphous powder and titanium hydride powder that make up the composite brazing filler metal.

[0091] Specifically, in step (3), the particle size of the nickel-based amorphous powder constituting the composite solder is 200-600 mesh, and the particle size of the titanium hydride powder is 600-800 mesh.

[0092] It should be noted that, in order to improve the wettability of the brazing filler powder on the surface to be soldered and to promote the interfacial bonding between the brazing filler and the titanium layer and nickel-based superalloy, the composite brazing filler needs to be prepared into a solder paste before use.

[0093] Specifically, in step (4), the nickel-based composite brazing filler metal is first prepared into solder paste, and then the solder paste is placed between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be soldered.

[0094] Specifically, the solder paste carrier is rosin, acrylic resin, etc., combined with at least one organic solvent such as acetone and isopropanol.

[0095] It should be noted that, in order to improve the wettability of the composite solder with the surface to be soldered, and to enable the solder paste to be formed and to exist stably between the surfaces to be soldered, the present invention needs to limit the ratio between the nickel-based composite solder, the paste carrier, and the solvent.

[0096] Specifically, the mass ratio of the nickel-based composite solder to the paste carrier and solvent is 1:(1-3):(5-8).

[0097] It should be noted that, in order to ensure the brazing connection strength while avoiding excessive content of brittle phase in the intermediate layer, which would affect the mechanical strength of the joint, the present invention needs to control the amount of solder paste used.

[0098] Specifically, in step (4), the thickness of the solder paste placed between the boron nitride ceramic and the nickel-based superalloy is 50-200 μm. If the solder paste is too thin, it will easily affect the interfacial bonding strength between the solder and the titanium layer and the nickel-based superalloy. If the thickness is too thick, the solder will have an erosion effect on the base material, which violates the original intention of brazing.

[0099] According to some preferred embodiments of the present invention, the thickness of the solder paste placed between the boron nitride ceramic and the nickel-based superalloy surfaces to be soldered can be any value in the range of 50-200mm, such as 50mm, 80mm, 100mm, 130mm, 150mm, 170mm, and 200mm.

[0100] It should be noted that, in order to ensure the bonding quality of the brazing interface while fixing the relative positions between the layers to be welded, the present invention requires the use of a mold to press the boron nitride ceramic and the nickel-based high-temperature alloy, which are placed between the surfaces to be welded with composite brazing filler metal, and to limit the pressing pressure.

[0101] Specifically, in step (4), a graphite mold is used to press the ceramic and alloy to be welded, wherein the pressure of the mold during pressing is 0.2-1 MPa. If the pressure is too high, the solder paste will be squeezed out between the surfaces to be welded; if the pressure is too low, the gases generated during the heat treatment process, including the gases generated by the thermal decomposition of the paste carrier and the hydrogen generated by the heated titanium hydride, will cause residual bubbles in the intermediate layer connecting the BN ceramic and the Ni-based superalloy, affecting the bonding strength of the joint interface.

[0102] According to some preferred embodiments of the present invention, the pressure of the mold during clamping can be any value in the range of 0.2-1MPa, such as 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, or 1MPa.

[0103] It should be noted that, in order to improve the interfacial bonding strength between the titanium layer and boron nitride, as well as the reaction between the titanium layer and the brazing filler metal, and to ensure that the physicochemical properties of the nickel-based superalloy are not affected by high temperature, and to maintain the intrinsic properties of the alloy to the greatest extent, this invention needs to limit the brazing heat treatment process steps and process parameters.

[0104] Specifically, in step (5), the heat treatment method includes: 3×10 -3 Pa ~ 5 × 10 -3 Under vacuum conditions, the temperature is raised to 1000℃-1100℃ and held for 5min-25min, then cooled. The vacuum environment of the heat treatment can prevent metallic Ti from being oxidized to TiO2, which would affect the solder reaction. The temperature and time of the heat treatment not only promote the solid-solid reaction between the titanium layer and boron nitride to form a TiN thin layer with a stronger bond to the substrate, but also prevent the physicochemical properties of nickel-based high-temperature alloys from being affected by high temperature.

[0105] According to some preferred embodiments of the present invention, the vacuum degree of the heat treatment of the present invention can be 3 × 10⁻⁶. -3 Pa ~ 5 × 10 -3 Any value within the range of Pa, such as 3 × 10 -3 Pa, 3.5 × 10 -3 Pa, 4×10 -3 Pa, 4.5 × 10 -3 Pa, 5×10 -3 Pa.

[0106] According to some preferred embodiments of the present invention, the heat treatment temperature of the present invention is any value in the range of 1000℃-1100℃, such as 1000℃, 1020℃, 1050℃, 1080℃, and 1100℃.

[0107] In some preferred embodiments of the present invention, the heat treatment time is any value within the range of 5 min to 25 min, such as 5 min, 7 min, 10 min, 12 min, 15 min, 18 min, 20 min, 23 min, and 25 min.

[0108] It should be noted that, in order to promote the discharge of gas during the heat treatment heating process and improve the interface bonding quality, the present invention needs to limit the rate of the heating process.

[0109] Specifically, in step (5), during the heat treatment process, the heating rate is 8℃ / min-12℃ / min. If the heating rate is too low, it will affect the heat treatment efficiency. If the heating rate is too high, it will easily lead to the gas generated by the thermal decomposition of the paste carrier (300-400℃) and the hydrogen volatilized from the decomposition of titanium hydride not being able to be discharged in time. This will result in bubbles in the intermediate layer formed by the interface reaction between the solder and the titanium layer and the alloy surface, affecting the strength. In addition, a suitable heating rate can also allow the titanium hydride in the composite solder to completely volatilize the hydrogen before the nickel-based amorphous solder melts and is brazed, so as to obtain pure Ti that truly plays a role in brazing, and timely and effectively prevent excessive reaction between the nickel-based amorphous alloy and the Ti layer.

[0110] It should be noted that, in order to avoid excessive thermal stress concentration caused by the difference in thermal expansion coefficients between different material layers during the heat treatment cooling process, which could lead to interface cracks and joint failure, the present invention needs to limit the cooling method.

[0111] Specifically, in step (5), the heat treatment cooling process includes: first reducing the temperature to 400-500℃ at a rate of 2-6℃ / min, and then furnace cooling to room temperature. Because the heat treatment temperature is too high, during the cooling and solidification process in the high-temperature section (500-1100℃), it is necessary to continue heating to control the slow cooling of the joint and avoid thermal stress cracking at the brazing filler metal reaction interface; when the temperature reaches the low-temperature section, the joint can be slowly cooled down with the furnace.

[0112] The connection joint based on boron nitride ceramics and nickel-based superalloys prepared by the method of this invention not only enables effective (crack-free interfacial bonding intermediate layer) and high bonding strength (shear strength up to 3.48 MPa at room temperature) connection between BN ceramics and nickel-based superalloys, but also preserves the intrinsic properties of Ni-based superalloys to the greatest extent. This allows the effectively connected BN ceramics to truly function as a high-temperature thermal structural material for thermal management, which is beneficial for the promotion and application of BN ceramics in aerospace, nuclear energy and other fields.

[0113] The present invention will be further explained and illustrated below through examples and comparative examples.

[0114] Example 1

[0115] A connection joint between boron nitride ceramic and nickel-based superalloy, specifically comprising:

[0116] (1) The surfaces to be welded of GH4169 nickel-based high-temperature alloy and h-BN ceramic were polished with 1000 grit sandpaper and then ultrasonically cleaned with acetone for 10 min.

[0117] (2) The cleaned h-BN workpiece to be welded is placed into a magnetron sputtering equipment for magnetron sputtering titanium film deposition. The conditions include: a base vacuum of 5×10⁻⁶. -5 Pa, argon pressure 1 Pa, DC power supply power 200 W, coating time 6 h, a 3 μm thick titanium film was obtained on the h-BN ceramic surface.

[0118] (3) Nickel-based amorphous brazing filler powder (200 mesh) and titanium hydride powder (400 mesh) with a mass ratio of 9:1 were placed in a vacuum ball mill jar, vacuum was drawn, and nitrogen gas of 0.2 MPa was injected for protection. The ball-to-filler ratio was 15:1. The horizontal ball mill was rotated at 120 r / min and ground for 10 min to obtain a composite brazing filler. The composite brazing filler was then mixed with a solvent and a paste carrier to obtain a composite brazing filler paste. The mass ratio of the composite brazing filler to the solvent and paste carrier was 1:3:5.

[0119] (4) Place the composite solder paste obtained in step (3) between GH4169 and the coated hexagonal boron nitride ceramic to be soldered, with a thickness of 100mm, and press it with a graphite mold with a pressure of about 0.4MPa.

[0120] (5) Place it in a vacuum furnace and wait for the vacuum degree of the vacuum furnace to reach 4×10 -3 At Pa, the heating process involves raising the temperature to 1050℃ at a rate of 10℃ / min and holding it for 15min; then lowering the temperature to 400℃ at a rate of 5℃ / min, shutting off the heating, and allowing the furnace to cool to room temperature, thus obtaining the connection joint between h-BN ceramic and GH4169 nickel-based superalloy. The actual connection joint is shown in the image. Figure 3 As shown, the SEM image of connector 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that nickel-based superalloys and BN ceramics can achieve a tight bond at the microscopic level; the test results show that the shear strength of the joint at room temperature reaches 3.48 MPa.

[0121] Example 2

[0122] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (2), the coating time was 4 hours, and a 2 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 3.24 MPa.

[0123] Example 3

[0124] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (2), the coating time was 2 hours, and a 1 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 2.99 MPa.

[0125] Example 4

[0126] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (3), the mass ratio of nickel-based amorphous brazing filler powder (200 mesh) to titanium hydride powder (400 mesh) was 8:2, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature reached 1.50 MPa.

[0127] Example 5

[0128] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 4. The difference was that in step (2), the coating time was 4 hours, and a 2 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 3.39 MPa.

[0129] Example 6

[0130] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 4. The difference was that in step (2), the coating time was 2 hours, and a 1 μm thick titanium film was obtained on the surface of the h-BN ceramic, and finally the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was obtained. The shear strength of the connection joint at room temperature reached 1.85 MPa.

[0131] Example 7

[0132] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 3. The difference was that in step (3), the mass ratio of nickel-based amorphous brazing filler powder (200 mesh) to titanium hydride powder (400 mesh) was 7:3, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature reached 1.24 MPa.

[0133] Example 8

[0134] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (4), the thickness of the solder paste placed between GH4169 and the coated hexagonal boron nitride ceramic to be soldered was 150 mm, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature reached 3.32 MPa.

[0135] Example 9

[0136] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that step (2) was not included, i.e., no titanium layer was prepared on the surface of the BN ceramic in Comparative Example 1. The connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature was tested to be 0.4 MPa.

[0137] Example 10

[0138] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (2), the coating time was 1 hour, and a 0.5 μm thick titanium film was obtained on the surface of the h-BN ceramic, finally obtaining the connection joint between h-BN ceramic and GH4169 nickel-based superalloy. The connection joint obtained by this method did not have a titanium layer, and the shear strength of the connection joint at room temperature was 0.52 MPa.

[0139] Example 11

[0140] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (5), the temperature was increased to 1000°C, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature was 2.95 MPa.

[0141] Example 12

[0142] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (5), the temperature was increased to 1100°C, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature was tested to be 3.26 MPa.

[0143] Example 13

[0144] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (5), the holding time was 25 min, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. The shear strength of the connection joint at room temperature was 3.15 MPa.

[0145] Comparative Example 1

[0146] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based high-temperature alloy was prepared using the same method as in Example 1. The difference was that in step (2), the coating time was 8h, and a 4μm thick titanium film was obtained on the surface of the h-BN ceramic. The connection joint could not be obtained by using the method of Comparative Example 1 because the titanium film was too thick, which caused the titanium layer to crack during the heat treatment process.

[0147] Comparative Example 2

[0148] The same method as in Example 1 was used to prepare a connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based high-temperature alloy. The difference was that in step (4), the thickness of the solder paste placed between GH4169 and the soldering surface of the coated hexagonal boron nitride ceramic was 300 mm. The resulting connection joint did not form an effective connection, and the macroscopic fracture location was located in the middle of the solder.

[0149] Comparative Example 3

[0150] The connection joint based on hexagonal boron nitride ceramic and GH4169 nickel-based superalloy was prepared using the same method as in Example 1. The difference was that in step (5), the temperature was raised to 1150°C, and the connection joint of h-BN ceramic and GH4169 nickel-based superalloy was finally obtained. After testing, the GH4169 nickel-based superalloy in the connection joint 16 showed obvious grain coarsening and softening.

[0151] The structural composition, dimensional parameters, and connection performance characterization of the connectors obtained using the above embodiments and comparative examples are shown in Table 1:

[0152] Table 1. Structural composition, dimensional parameters, and performance characteristics of the connection joints in the embodiments and comparative examples.

[0153]

[0154]

[0155] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A connecting joint between boron nitride ceramic and nickel-based superalloy, characterized in that, The connector comprises a boron nitride ceramic, an intermediate layer, and a nickel-based superalloy connected in sequence. The intermediate layer, from the boron nitride ceramic to the nickel-based superalloy, comprises a solder-boron nitride reaction layer, a solder reaction layer, and a solder-nickel-based superalloy reaction layer. The solder-boron nitride reaction layer is formed by reacting nickel-containing solder with boron nitride, and contains TiN and TiB2. The method for preparing the connecting joint includes: (1) Prepare nickel-based composite solder, wherein the nickel-based composite solder comprises nickel-based amorphous powder and titanium hydride powder, wherein the mass ratio of nickel-based amorphous powder to titanium hydride powder is 7:3 to 9:1; and the nickel-based amorphous powder comprises, by weight percentage, 2.75%-3.5% B, 4%-5% Si, 6.0%-8.0% Cr, 2.5%-3.5% Fe, ≤0.06% carbon, and the balance being Ni; (2) Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it with a mold; (3) Heat treatment to obtain the connecting joint, wherein the heat treatment method specifically includes: 3×10 -3 Pa ~ 5 × 10 -3 Under vacuum conditions, the temperature is raised to 1000℃-1100℃, held for 5min-25min, and then cooled. The heating rate is 8℃ / min-12℃ / min. The cooling process specifically includes: first reducing the temperature to 400-500℃ at a rate of 2-6℃ / min, and then furnace cooling to room temperature. Before step (2), a titanium film is deposited on the surface of the boron nitride ceramic to be welded.

2. The connecting joint according to claim 1, characterized in that, The solder-boron nitride reaction layer includes a boron nitride-Ti layer reaction layer, a Ti layer, and a solder-Ti layer reaction layer.

3. The connecting joint according to claim 1 or 2, characterized in that, The boron nitride ceramic is a hexagonal boron nitride ceramic; And / or, the boron nitride ceramic is in the form of sheets or blocks.

4. The connecting joint according to claim 2, characterized in that, The boron nitride-Ti layer reaction layer contains TiN; And / or, the thickness of the boron nitride-Ti layer reaction layer is 0.1-0.5 μm.

5. The connecting joint according to claim 2, characterized in that, The thickness of the Ti layer is 1-4 μm; And / or, the thickness of the solder-Ti layer reaction layer is 0.1-0.5 μm.

6. The connecting joint according to claim 1 or 2, characterized in that, The thickness of the solder reaction layer is 20-200 μm.

7. The connecting joint according to claim 1 or 2, characterized in that, The brazing filler metal-nickel-based superalloy reaction layer is a metal cladding layer.

8. The connecting joint according to claim 7, characterized in that, The thickness of the metal cladding layer is 5-25 μm.

9. The connecting joint according to claim 1 or 2, characterized in that, The shear strength of the connection joint is 0.4-4 MPa.

10. A method for preparing the connecting joint between boron nitride ceramic and nickel-based superalloy as described in claim 1, characterized in that, The method includes: (1) Preparation of nickel-based composite solder; (2) Place the nickel-based composite brazing filler metal between the boron nitride ceramic and the nickel-based high-temperature alloy surfaces to be welded, and press it with a mold; (3) Heat treatment to obtain the connecting joint.

11. The method according to claim 10, characterized in that, Before step (2), a titanium film is deposited on the surface of the boron nitride ceramic to be welded.

Citation Information

Patent Citations

  • Braze welding method of composite powder used for carbon / silicon carbide and niobium or niobium alloy

    CN101239836A

  • Brazing method for ceramic and metal

    CN109734469A